A Note on LP-Sasakian Manifolds with Almost Quasi-Yamabe Solitons - Sunil Kumar Yadav; D. L. Suthar; Biniyam Shimelis (Journal of Mathematics)
We categorize almost quasi-Yamabe solitons on LP-Sasakian manifolds and their CR-submanifolds whose potential vector field is torse-forming, admitting a generalized symmetric metric connection of type α,β. Finally, a nontrivial example is provided to confirm some of our results.